Problem of the hill tribes : North-East frontier, 1873-1962 (Vol.3) - Barpujari, H.K. (Gauhati, 1981)
This book, the last of the series, deals mainly with tribes which remained unsubdued or beyond the pale of British influence till the closing years of the last century. It opens with the boundary disputes with the Nagas which continue to plague even now the relations with their neighbours in the plains, As a pan acea followed the Inner Line which sought to debar over-zealous frontier officers, except under compelling circumstances, from meddling into affairs of these tribes. What were the forces and factors which compelled the authorities in England and India to replace non intervention by a policy of gradual advance until the entire tract on this side of the Patkals on the one hand and the frontier of Burma on the other was brought under administrative or political control? What were the causes in reality which occasioned out rages and out-breaks leading to punitive expeditions, subjugations and domination? What were the constraints that forced Whitehall to adhere strictly to leissez faire towards tribes in the north 2 These are some of the questions which this book seeks to explain. Apart from the heroic defence of the hillmen of their hills and fastnesses, the narrative throws light on the political acumen and administrative abilities of a team of frontier officials who were not shadowy beings but living personallties, firm in dealing with evil-doers but ever conciliatory and easily accessible to all who brought their troubles to their doors.
Keywords: Tribes